Accrual-based, real activities earnings management and corporate social responsibility: A virtuous circle? emerging market evidence - Nguyen Vinh Khuong; Huynh Thi Ngoc Ly; Le Huu Tuan Anh (Cogent Economics & Finance, 2023)
AbstractThe relationship between Earnings Management (EM) and Corporate Social Responsibilities (CSR) has raised a considerable number of attentions, especially, in financial and accounting field since they determine firms’ performance as well as market positioning. On the contrary, in an emerging country as Vietnam, the number of relevant studies are rare together with several limitations. Thus, this paper is the pioneer investigating the cause and effect among Accruals Earnings Management (AEM), Real Earnings Management (REM) as two proxies for EM, and CSR. Next, Granger’s causality replacing for traditional method is employed in order to interpret this nexus. The analysis relies on the sample size of 225 companies during the period 2014–2018 from Hanoi Stock Exchange (HNX) and Ho Chi Minh Stock Exchange (HOSE). We figured out executives prefer REM to AEM when implementing earnings manipulations. Consistent with the expectations and prior scholars, we found there is a negative correlation in the association of AEM and CSR while it is positive in the case of REM and CSR. Besides the consistent results with multivariate regression analysis (MRA) in terms of CSR-EM association, the fsQCA findings also explore more combinations regarding the relationship between CSR-EM. Additionally, all empirical results also provide evidence that there is cause-and-effect relationship in terms of AEM, REM and CSR which has never been researched and discussed over the past several years.